Core-periphery patterns across the European Union : case studies and lessons from eastern and southern Europe - Da Silva Duarte, Maria Adelaide Pedrosa; Carmen Pascariu, Gabriela (Emerald Publishing Limited, 2017)
The EMU debt crisis that emerged in 2010 has identified a group of Southern countries, especially Greece, Portugal, Spain and Italy, as low performers exhibiting several seriousmacroeconomic imbalances, and it has also highlighted that EU integration experiencedby Eastern European countries (especially the latter-comers to EU) was not accompanied by a rapid process of real convergence. Since then, the researchabout the effects of peripherality have regained a renewed interest toultimately ground better regional policy recommendations aimed at achieving asustained reduction of income per capita disparities across EU regions. In this new work, Pascariu and Duarte, along with an international group ofacclaimed scholars, delve into key challenges currently facing the EuropeanUnion. They investigate this central question: does the domestic market systemlead to the development of a center-periphery model, by highlight gaps, or doesit support the convergence process? Analyzing the effects of peripheralityacross the EU regions, a two-fold approach is used to deliver policyrecommendations grounded in economic theory, and of interest to other countriesand regions facing a process of integration.
Includes index.
Includes bibliographical references.
Print version record
Keywords: European Union -- Case studies; Business & Economics -- Economics -- General; International economics